RANCANG BANGUN APLIKASI SISTEM PAKAR UNTUK KERUSAKAN KOMPUTER DENGAN METODE BACKWARD CHAINING - Minarni, S. Si., M.T; Rahmad Hidayat, ST (ITP Press, 2013)
he computer is a machine that can be damaged in carrying out its functions. To provide such information, it takes knowledge of a computer expert. Expert system designed as a computer program, so the expert system program can provide information like a computer expert who always stand beside the computer itself. Method is by using backward chaining, expert system for computer do trace to retreat wet backward, starting from the hypothesis and then looking for evidence supporting or opposing. Expert system for computer damage will provide information and solutions to computer users on issues relating to damage the hardware computer quickly.